Mempelajari IPA Dapat Meningkatkan Keimanan dan Moral Siswa MI - Rahmansyah, Syahrul (Bedelau: Journal of Education and Learning, 2023)
Basic education has a strategic role in shaping students' character and morals from an early age. Integration between science and religion in the learning process, especially in the subject of Natural Sciences (IPA), is one of the effective approaches to strengthen faith and instill moral values ​​based on Islamic teachings. Learning Natural Sciences associated with Islamic principles can help students understand the order of nature as a manifestation of the greatness of God, while fostering their awareness of responsibilities in protecting the environment and social life. This study aims to analyze how science learning can contribute to increasing the faith and morals of students in Madrasah Ibtidaiyah (MI) by applying a qualitative approach through case study methods and surveys. Data obtained through observation, interviews, as well as the distribution of questionnaires to students, teachers, and educators at MIN 3 Pekanbaru who have implementing the integration between Natural Sciences and Islamic values. The results showed that as many as 82% of students felt more responsible in protecting the environment after understanding the concept of ecosystem balance in Islamic perspectives, 76% of students experienced an increase in awareness of living things, and 79% of students became more disciplined after studying the order of nature through science concepts. This research has a significant impact on Islamic education, where the integrative approach in learning science is proven to be able to increase student spiritual and moral awareness. The results of this study can be a reference in the development of a more holistic curriculum, combining science with Islamic values. Thus, science learning is not only a means of transferring knowledge, but also plays a role in shaping the character of students who believe, moral, and responsible in everyday life